Esketamine opioid-free intravenous anesthesia versus opioid intravenous anesthesia in spontaneous ventilation video-assisted thoracic surgery: a randomized controlled trial - Fan, Qisen; Luo, Jinhui; Zhou, Qianling; Zhang, Yaoliang; Zhang, Xin; Li, Jiayang; Jiang, Long; Lan, Lan (Frontiers in Oncology, 2023)
Background: opioid-free anesthesia provides adequate analgesia and can reduce postoperative opioid use, but has not been demonstrated in spontaneous ventilation video-assisted thoracic surgery (SV-VATS). Methods: We identified 60 eligible patients (opioid-free group: n=30; opioid group: n=30) between 2022.9.15 and 2022.12.15 from The First Hospital of Guangzhou Medical University. Patients were randomized to receive standard balanced opioid-free anesthesia (OFA) with esketamine or opioid anesthesia (OA) with remifentanil combined with sufentanil. All patients received intraoperative propofol, midazolam, dexmedetomidine, intercostal nerve block, and postoperative oral ericiclib for pain control. The primary outcome was the pain numeric rating score (NRS) at 48 h postoperatively, and secondary outcomes were intraoperative respiratory and circulatory indices, opioid consumption, vasoactive drug dosage, and recovery in the post anesthesia care unit (PACU) and ward. Results: In this study, 60 patients were included. There was no significant difference between the opioid-free group and the opioid group in the postoperative pain control and recovery quality. The opioid-free group was associated with significantly decreased in the total dose of phenylephrine (P=0.001) and the incidence of hypotension (P=0.004) during operation, the recovery time of spontaneous respiration was short (P＜0.001), the quality of lung collapse was higher (P=0.02). However, the total dosage of propofol (P=0.03) and dexmetomidine (P=0.02) increased significantly, the awakening time was prolonged (P=0.039). Conclusions: Compared with opioid anesthesia, opioid-free anesthesia has more advantages in maintaining circulatory and respiratory stability, improving the quality of pulmonary collapse in SV-VATS.